Irradiation induced enhancement of ferromagnetic τ-phase in MnAl alloy thin films on Si substrate. (1st February 2019) - Khanduri, H; Khan, S A; Srivastava, S K; Sulania, I; Chandra, M; Link, J; Stern, R; Avasthi, D K
Abstract: Ferromagnetic L10 MnAl phase was achieved in as-grown MnAl alloy thin films by using 250 keV H + ion irradiation without conventional post annealing. The magnetic properties and crystallinity of MnAl thin film got modified with increase in irradiation fluence. The magnetic coercivity was found to be maximum (2500 Oe) at the fluence of 5 × 10 14 ions cm −2 . The hysteresis curve for the sample irradiated by H + ions with fluence of 5 × 10 16 ions cm −2 exhibited highest saturation magnetization (130 emu/cc) among all irradiated films. The increase in irradiation fluence led to larger grain growth as confirmed from AFM results. The magnetic domain pattern observed by MFM images confirmed the presence of ferromagnetic τ -phase in irradiated samples. The present study establishes that the H + ion-irradiation can be an effective technique to tailor the structural as well as magnetic properties of MnAl thin films.